2020
DOI: 10.3390/microorganisms8010114
|View full text |Cite
|
Sign up to set email alerts
|

Broader Geographical Distribution of Toscana Virus in the Mediterranean Region Suggests the Existence of Larger Varieties of Sand Fly Vectors

Abstract: Toscana virus (TOSV) is endemic in the Mediterranean basin, where it is transmitted by sand flies. TOSV can infect humans and cause febrile illness as well as neuroinvasive infections affecting the central and peripheral nervous systems. Although TOSV is a significant human pathogen, it remains neglected and there are consequently many gaps of knowledge. Recent seroepidemiology studies and case reports showed that TOSV’s geographic distribution is much wider than was assumed a decade ago. The apparent extensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 79 publications
0
21
0
Order By: Relevance
“…Toscana virus-related viruses, sandfly fever Naples virus-related viruses, and Massilia virus-related viruses have been detected in Phlebotomus perfiliewi and Phlebotomus perniciosus sandflies. A recent study suggested that the spectrum of competent sandfly vector species for Toscana virus-related viruses is broader than previously thought and includes Phlebotomus longicuspis , Phlebotomus sergenti , Phlebotomus tobbi , Phlebotomus neglectus , and Sergentomyia minuta ( 28 ). Rodents have been found to be infected with Gordil virus and Saint Floris virus, although the associated sandfly vector remains elusive ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Toscana virus-related viruses, sandfly fever Naples virus-related viruses, and Massilia virus-related viruses have been detected in Phlebotomus perfiliewi and Phlebotomus perniciosus sandflies. A recent study suggested that the spectrum of competent sandfly vector species for Toscana virus-related viruses is broader than previously thought and includes Phlebotomus longicuspis , Phlebotomus sergenti , Phlebotomus tobbi , Phlebotomus neglectus , and Sergentomyia minuta ( 28 ). Rodents have been found to be infected with Gordil virus and Saint Floris virus, although the associated sandfly vector remains elusive ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are circa 900 species already described, and 70 of these species have been reported as potential vectors of Leishmania spp. with few others involved in the natural transmission of viruses, such as Phlebovirus ( Reoviridae family) [ 31 ]. These insects are still capable of harboring other microorganisms, since they have contact with different environments and substrates [ 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies are required to evaluate if these pathogens circulate in the sand fly populations in Germany. This situation might change in future if sand fly species expand in range due to climate change and build up larger populations [30]. In addition, further studies are necessary to clearly characterize the environmental conditions of the habitats of P. mascittii.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports of seroepidemiological studies showed that the geographical distribution of Toscana virus is much wider than previously assumed and despite its importance as a human pathogen, it remains neglected and there are consequently many gaps of knowledge [30]. Especially during outdoor activities, the exposure to sand flies can increase the risk of an infection with phleboviruses [31].…”
Section: Introductionmentioning
confidence: 99%